Endoscopic removal of a metal stent that migrated into the peritoneal cavity after endoscopic ultrasound‐guided hepaticogastrostomy. Issue 3 (29th March 2019) - Fujisawa, Toshio; Saito, Hiroaki; Isayama, Hiroyuki
Abstract : Watch a video of this article